Additions to the Bromeliaceae family in Veracruz, Mexico - Rivera-Hernández, Jaime Ernesto; Vargas-Rueda, Abel Felipe; Torres-Cantú, Gerardo Benjamín; Alcántara-Salinas, Graciela; Cházaro-Basáñez, Miguel de Jesús; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo (Instituto de Ecología, A.C., 2020)
Background and Aims: The Bromeliaceae family in Mexico is made up of 422 species, of which 96(22.7%) are found in Veracruz. Ten of these species are endemic to the state. The objective of this study was to identify and report the bromeliad species that had not been recorded in the entity. Methods: Botanical expeditions were carried out in different regions of the state of Veracruz as part of the research of two doctoral theses. Additionally, collections of Bromeliaceae in the herbaria CORU and XAL were revised. Key results: We documented new state records for Veracruz of two species of the genus Tillandsia (T. bourgaei y T. roseoscapa) and one species of Pitcairnia (P. xanthocalyx). Another species (Tillandsia prodigiosa) represents a rediscovery for the state´s flora. Finally, information regarding distribution and habitat, as well as photographs of each species, are presented. Conclusions: The results obtained, together with other new previously reported records, confirm that the central zone of Veracruz state, especially the Córdoba-Orizaba-Zongolica zone, had remained, until recently, poorly studied from the floristic point of view, highlighting the importance of xerophytic vegetation present in the area, where species occur that are shared with the flora of Tehuacán-Cuicatlán valley. The same applies to the northern portion of the state, in the Totonacapan region, which has received little attention from Mexican botanists.